2012
DOI: 10.1021/mp300298z
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Desorption of Liquid Excipients Reduces the in Vitro and in Vivo Performance of Self-Emulsifying Drug Delivery Systems Solidified by Adsorption onto an Inorganic Mesoporous Carrier

Abstract: The purpose of the current study was to provide a mechanistic basis for in vitro and in vivo performance differences between lipid-based formulations solidified by adsorption onto a high surface area material and their respective liquid (i.e., nonadsorbed) counterparts. Two self-emulsifying formulations (based on either medium-chain or long-chain lipids) of the poorly water-soluble drug danazol were solidified by adsorption onto Neusilin US2. Liquid and adsorbed lipid-based formulations were subjected to in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(73 citation statements)
references
References 45 publications
9
63
0
1
Order By: Relevance
“…The obtained observations are comparable with Kang et al who reported slow and incomplete ibuprofen release from SMEDD formulation loaded with MAS [32]. In addition, Van Speybroeck et al observed incomplete desorption of danazol through MAS loaded SMEDD formulation [11]. Various researchers had attempted to determine the reason behind the poor release through adsorbent formulations.…”
Section: Oil Desorption Studysupporting
confidence: 83%
See 3 more Smart Citations
“…The obtained observations are comparable with Kang et al who reported slow and incomplete ibuprofen release from SMEDD formulation loaded with MAS [32]. In addition, Van Speybroeck et al observed incomplete desorption of danazol through MAS loaded SMEDD formulation [11]. Various researchers had attempted to determine the reason behind the poor release through adsorbent formulations.…”
Section: Oil Desorption Studysupporting
confidence: 83%
“…Further understanding of the molecular determinants of the interaction with MAS was beyond the scope of the current study, but is the subject of ongoing investigations. Furthermore, it is reported Brought to you by | NDSU Library Periodicals Authenticated Download Date | 7/25/15 4:27 PM that Cremophor EL has affinity to MAS causing a reduction in danazol release from the solid SMEDDS [11]. To better understand the role of silanol/hydroxyl groups in the interaction with the liquids calcination was performed to reduce the possibility of H-bonding.…”
Section: Effect Of Surfactant and Surface Silanols On Oil Desorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17] In recent years, microemulsions have become an efficient approach to improving the solubility and poor oral bioavailability of insoluble drugs. [18][19][20] Given the relative low intestinal absorption of triterpene and adlay seed oil, introduction of microemulsion technology into the Ling-Yi formulation might be helpful in overcoming its intrinsic disadvantages, improving its bioavailability, and enhancing its therapeutic effect. However, a microemulsion containing a high concentration of a pharmaceutical adjuvant could potentially have a detrimental effect on normal body tissue.…”
Section: Introductionmentioning
confidence: 99%